Decreased dihydroartemisinin-piperaquine protection against recurrent malaria associated with Plasmodium falciparum plasmepsin 3 copy number variation in Africa. - Pernaute-Lau, Leyre (2025)
Department of Microbiology and Tumour Cell Biology. Karolinska Institutet. Stckholm, Sweden. / Biosystems & Integrative Sciences Institute. Faculty of Sciences. University of Lisbon. Lisbon, Portugal. / The Art of Discovery. Derio, Basque Country, Spain.